Corporate Culture Communication Process Through Invitational Rhetoric at Tung Desem Waringin (TDW) Group - Hojanto, Ongky; Jamalullail, Jamalullail (Jurnal Mamangan, 2023)
TDW Group is a holding company founded by Tung Desem Waringin who is known as: The Best Speaker in Indonesia according to Marketing Magazine. Business leaders who have employees with diverse backgrounds, ages, cultures, knowledge, and experiences need an effective way to communicate with them. The interpretive approach is adopted from a practical orientation. The purpose of this study is to interpret behavior in detail by conducting direct observations of opinions and ideas that are valued (immanent value) as indicated by the absence of objections and interruptions when participants share experiences and other participants are actively involved in writing conclusions through the comments column. Through qualitative research with the triangulation method, the data analysis process uses NVivo. The final result of this study found an effective corporate culture communication process, easy to understand and embedded into work habits. Based on the results and discussion, it can be concluded that participants are encouraged to involve themselves (self-determination) because they feel invited (to invite), involved (to enfold), their ideas are valued (meaningful) and listened to (to listen).